Hybrid simulation method by cooperating between manufacturing system simulation and computational fluid dynamics simulation (Evaluation for simultaneous operation of production lines and compressed air systems, and evaluation for energy consumption per unit of production throughput) - Hitoshi NAGASAWA; Hironori HIBINO; Motonobu HASHIMOTO; Norihumi KASE (Nihon Kikai Gakkai ronbunshu, 2018)
For enhancing the energy efficiency of a manufacturing system as a whole, it is critical to optimize energy consumption including that in the utility systems, which supplies compressed air, and that in each production line. Compressed air is used in the manufacturing domain in a wide variety of systems such as those that fix and hold works through pneumatic equipment. Compressed air systems account for approximately 10% of the industrial electricity consumption in the European Union. Therefore, a method for minimizing the energy used in compressed air systems is sought. From the point of view of energy saving in the operation of a compressed air system, a method is available for reducing the output of the compressed air system. However, if the supply of compressed air becomes insufficient by the reduction in the amount supplied, it can result in extension of the cycle time of the production line or in defective products; thus, it can eventually cause lower productivity. Therefore, businesses ensure adequate supply from compressed air systems in order to prevent the adverse impact of insufficient supply of compressed air on productivity; however, this results in wastage of energy. Therefore, it is necessary to simultaneously evaluate productivity and compressed air feed. However, there has been no progress in the research of methods for evaluation. Hence, in this research, a method, which is a hybrid of a manufacturing system simulation and computational fluid dynamics simulation, is proposed for evaluating the operation of both production lines and compressed air systems simultaneously. The proposed method is used to evaluate the deficiencies and excesses in the supply from a compressed air system and the reliability of the supply of a compressed air system in response to the daily production schedule. Moreover, the energy consumption per unit of production throughput is evaluated.